CONJUGATION PROBLEM WITH MULTIPOINT CONDITIONS FOR MIXED HYPERBOLIC TYPE EQUATIONS - Medvid, O. M.; Savka, I. Ya.; Tymkiv, I. R. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The conditions of correct solvability in the Sobolev spaces of the conjugation problem with local multipoint conditions and periodic conditions for higher order mixed hyperbolic type equations is obtained. It has been proved that these conditions fulfill for almost all (with respect to the Lebesgue measure) vectors made up of the nodes of multipoint conditions.